From trial data to practical knowledge: qualitative study of how general practitioners have accessed and used evidence about statin drugs in their management of hypercholesterolaemia - Fairhurst, Karen (British Medical Journal, 1998)
Objectives To explore how general practitioners have accessed and evaluated evidence from trials on the use of statin lipid lowering drugs and incorporated this evidence into their practice. To draw out the practical implications of this study for strategies to integrate clinical evidence into general medical practice. Design Qualitative analysis of semistructured interviews. Setting General practices in Lothian. Subjects 24 general practitioners selected to obtain a heterogeneous sample. Results Respondents were generally aware of the evidence relating to the use of statins in secondary prevention of coronary heart disease, but they were less clear about the evidence in primary prevention. The benefits of statins in secondary prevention were clearer to them and the social and economic issues less complex than was the case for use in primary prevention. Respondents rarely said they appraised the methods and content of trials, rather they judged the trustworthiness of the source of trial evidence and interpreted it within the context of the economic and social factors which impinge on their practice. Moreover, trial data become relevant for routine practice only when underpinned by a consensus on these issues. Conclusion Strategies to promote incorporation of evidence from clinical trials into everyday practice are likely to be effective if they tap into and build on the process of local consensus building. Strategies such as teaching critical appraisal skills and guideline development may have little effect if they are separated from this process.